EPS RHA concrete bricks - A new building material - Ling,, I. H; Teo,, D.C.L. (Jordan University of Science and Technology, 2013)
Reuse of agricultural wastes and industrial by-products for building materials has been gaining popularity in the recent years. Agricultural waste material; namely rice husk ash (RHA), and industrial by-product; namely expanded polystyrene beads (EPS) are discarded in large amounts globally, causing increased environmental problems. Therefore, this paper introduces innovative efforts of the combined use of RHA and EPS wastes for the production of EPS RHA lightweight concrete bricks. Results showed that the commercial development of EPS RHA bricks is not only highly promising but also effectively sequestering the accumulation of these waste materials